THE MISSION OF HIGHER EDUCATION - Éva Sándor Kriszt (Sekolah Tinggi Maritim Yogyakarta, 2016)
Perhaps the most obvious responsibility of higher education is the education of young (and often not-so-young) professionals. Another very important function is research, and it has other important functions, but here we will be concerned mainly with its educational function. How it can fulfill this function can be measured by examining what benefits it can provide (or more precisely: has provided) to the target group (the graduates). This – the “return of investment” – can be measured by considering the rewards appearing is the form of better jobs, higher remuneration or other forms of appreciation. Some of these can be expressed in monetary terms; others (such as self-fulfilment or more favourable working conditions) cannot be quantified so easily.